Increasing MSME's Competitiveness in East Java: E-IEM Alternative Applications Based on E-Commerce to Increase Productivity, Output Growth and Market Share - Mufid ,M. Lutfi, Dahlan Yuli S (University of Respati Yogyakarta, Indonesia, 2019)
MSME’s (Micro Small Medium Enterprises) plays an important sector to drive the economic productivity of acountry. In Indonesia 99% of businesses come from MSME’S, 97% of workers depend on the MSME’s sector,and 57% contribute to Indonesia's GDP. However, the problems faced by MSME's today are related to thecapacity and quality of human resources, as well as access to productive resources and markets. MSME's alsoneeds to increase its resilience in its business in conditions of increasing business competition and changes inmarket demand caused by technological developments.Referring to this problem, a trading platform in the form of an internet platform is needed to reduce theseproblems. E-Commerce is a trading platform that utilizes the advancement of internet Technology to facilitate theoccurrence of buying and selling transactions. E- Commerce is very profitable for producers and consumers,because it can reduce costs and time efficiency for both parties.E-Commerce that will be made by researchers is E-IEM (E-Integrated Education Marketing). This applicationprovides access to superior product information from MSME’s in an area and sells it to the general public. Inaddition, this application also provides guidance on MSME's starting from the beginning of opening a businessuntil it is steady. E-IEM will be a forum for MSME's to sell products easily domestically and abroad. So theproblems faced by MSME's can be overcome. Writing this scientific paper uses secondary data and primary withqualitative descriptive writing method. To be able to create the validity of information about the E-IEM applicationresearchers plan to work with the East Java Provincial Government Communication Committee to get the data.So E-IEM is expected to be able to increase sales, productivity and market share effectively and efficiently